Market assessment on the potential of oil palm empty fruit bunch (OPEFB) particleboard in Malaysia's wood-based industries - Muhammad, Ismail; Ratnasingam, Jegatheswaran; Mohamed, Shukri; Mohamad Kasim, Mohamad Roslan; Kamal, Izran (Universiti Putra Malaysia Press, 2012)
This study was undertaken to assess the market potential and perceptions of oil palm empty fruit bunch (OPEFB) particleboards in Malaysia's wood-based industries, including furniture. The results of the assessments were based on the reasons and opinions raised by the wood-based product manufacturers and users. The assessment was conducted through a survey which involved 300 respondents during Malaysian International Furniture Fair (MIFF) and Malaysian Furniture Exporters Exhibition (MAFEX) in March 2009 with the aims to investigate the manufacturers' and users' awareness and perceptions towards OPEFB particleboards as an industrial material, to identify OPEFB particleboard potential as an input material and to give general recommendations to OPEFB-based manufacturers, particularly particleboards, so as to help them improving their products based on analysis of the product strengths and weaknesses. The survey data obtained from the fair and exhibition were transformed into tabular and graphical forms. A descriptive analysis was performed for the gathered data to make them interpretable. The 'reasons for choosing' data were analysed with respect the Normality Test by using Kolmogrov-Smirnov Test to determine whether the data are normal or not. The data are considered normal if the mean value is greater than 0.5. The survey showed that most of the respondents preferred rubberwood as a better raw material to be used in producing wood-based products compared to OPEFB. This is because promotion on OPEFB is insufficient and should be done more frequently and widely to gain attentions from wood-based product manufacturers.